The appearance and significance of Rastafari cultural aspects in South Africa - Midas Chawane (Contree)
This article explores the presence and importance of Rastafari cultural features in South Africa. These cultural aspects include symbols and language that have become popular in South Africa from 1997 when the movement was formalised.1 The symbols include religious signifiers employed in Rastafarianism such as the colours of Marcus Garvey, which are displayed in the attires worn by both Rastafarians and non-Rastafarians. While practices of symbolic investment include the growing of dreadlocks, and the use of “ganja” (marijuana) as a sacrament – these practices are frequently distilled into visual signifiers such as equating dreadlocked person with a lion and a “ganja” sign that appears on T-shirts and car stickers. Rastafarians have also coined a new language (“iry talk or dread language”) as their means of communication. In the wake of the democratic transition in 1994, both the language and symbols of the Rastafarian movement have gained increasing popularity in South Africa. By analysing specific examples of symbolic practice and visual signification within a historical framework, the article explores the meanings of Rastafarian language and symbolism for post-apartheid South Africa. While Rastafarian symbols have been adopted by various people for different reasons, their language has become popular among people outside the movement.